On unitary operators in weighted spaces A^2_ω(C) of entire functions - Rafayelyan, S. G.; Jerbashian, A. M. (Methods of Functional Analysis and Topology, 2008)
The paper gives a complete characterization of all unitary operators acting in some wide Hilbert spaces A^2_ω(C) of entire functions possessing weighted square integrable modulus over the whole finite complex plane, which exhaust the set of all entire functions.